PREDATORY PRICING PRACTICES IN TIKTOK SHOP IN THE STUDY OF ISLAMIC LAW - Anti Anfaul Lisani; Moch. Farich Alfani (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
Predatory pricing is another term for the practice of setting extremely low prices with the aim of forcing competitors out of business or forcing them to close their doors because they can no longer compete. Techniques such as cutting prices well below market prices to attract a large number of customers, but eventually, prices return to normal. This study examines how predatory pricing is viewed under Islamic law. This research consists of a literature study, which involves looking at resources related to the research subject, and library research, which involves surveying library materials to collect data using documentation procedures. The fundamental ideals and guiding concepts of Islamic business ethics, Tazkiyah, Khilafah, tauhid, and Ihsan, have been applied to the analysis process. Therefore, buying and selling in a manner that deviates from these guidelines is contrary to Islamic economics, mashlahah al-ummah, ethical theory, and Maqashid Sharia and fails to fulfil the intended objectives of economic law.